The Rise of Misinformation in the Digital Age: Moroccan Students' Attitudes and Perceptions of Fake News Online - Isam Mrah; Hicham Tizaoui (Journal of English Language Teaching and Linguistics, 2018)
As today’s students spend substantial time online, there is an increasing tendency to utilize the Internet as their primary source of information. With the proliferation of user-generated content platforms and the shrinking influence of traditional gatekeeping, there is a growing abundance of misinformation available to the public that coexists alongside accurate information. In this paper, we explored the attitudes and perceptions of teenage students towards misinformation online. To this end, a web-based survey was administered to both Moroccan high school teachers and students to collect and analyze their responses regarding the issue being debated. Additionally, the present study investigated the extent to which EFL textbooks in Morocco enable learners to build skills necessary for identifying fake news. The study adopted content analysis as the primary research method for data analysis and interpretation. The results obtained are in line with the hypothesis guiding this research that a fair majority of teenage students are vulnerable to misinformation online due in large to the overwhelming information overload available at the touch of a button along with their lack of exposure to effective strategies for processing information online.  Based on the findings obtained, schools are required to develop appropriate approaches to teach digital literacy skills, particularly in empowering young learners to distinguish credible sources from unreliable ones. Equally important, teachers are called upon to help students keep up with the new, fast-moving knowledge economy, which is driven by information and technology.